A kind of high-strength antibacterial and deodorizing socks

By adopting composite yarns and three-dimensional braiding technology, combined with nano-silver ion solution and other treatment agents, the shortcomings of existing socks in antibacterial and odor-proofing effects, strength, breathability and comfort are solved, and multiple functional effects of high strength, antibacterial, anti-odor, breathability and comfort are achieved.

CN119777150APending Publication Date: 2025-04-08JILIN SHUANGYUAN TEXTILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960442.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing socks have shortcomings in antibacterial and odorant effects, strength, breathability and comfort. The antibacterial and odorant effects are not lasting, insufficient strength, poor breathability and limited comfort.

Method used

Compound yarn and three-dimensional braiding technology are used to blend cotton fibers, elastic fibers, nylon fibers, polyester fibers and silver-based antibacterial fibers to form composite yarns with antibacterial function, and then mold them through three-dimensional braiding technology. Finally, it is impregnated by nano-silver ion solution and other treatment agents to form socks with tiny pore structures.

Benefits of technology

It significantly enhances the antibacterial and odorproof performance of socks, improves strength and durability, ensures good breathability and comfort, and is suitable for long-term wear and outdoor sports.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216968450000081
    Figure BDA0005216968450000081
Patent Text Reader

Abstract

The present invention relates to the technical field of socks, and in particular to a high-strength antibacterial and deodorizing socks. A composite yarn with an antibacterial function is formed by blending cotton fiber, elastic fiber, nylon fiber, polyester fiber, and silver-based antibacterial fiber, and then a sock with a microporous structure on the surface is formed by a three-dimensional stereoscopic knitting technology, and finally a finished sock is obtained after being impregnated with a treatment agent. The raw materials of the treatment agent are counted by weight: 1-5 parts of nano silver ion solution, 5-10 parts of aqueous polyurethane emulsion, 3-8 parts of acrylic resin, 1-3 parts of silane coupling agent, 0.5-2 parts of ultraviolet light blocking agent, 0.1-0.5 parts of defoaming agent, 1-2 parts of softener, and 70-80 parts of water. The present invention provides a high-strength antibacterial and deodorizing socks, which not only improves the strength and durability of the socks by using composite yarns and three-dimensional stereoscopic knitting technology, but also significantly enhances its antibacterial and deodorizing effect, while ensuring good air permeability and comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of socks, in particular to a pair of high-strength antibacterial and anti-odor socks. Background Art

[0002] As a necessity for daily wear, socks not only need to meet basic comfort and breathability, but also need to have certain antibacterial and anti-odor functions to prevent bacterial growth and odor on the feet. However, existing socks products have many deficiencies in terms of antibacterial and anti-odor effects, strength, breathability and comfort, which are specifically manifested in the following aspects:

[0003] (1) The antibacterial and deodorizing effects are not long-lasting: Many sock products use chemical antibacterial agents, which are easily ineffective after repeated washing, resulting in a decrease in the antibacterial and deodorizing effects.

[0004] (2) Insufficient strength: Traditional socks are prone to wear and tear when worn for long periods of time or during outdoor activities, especially in the toes and heels, which are prone to holes or damage.

[0005] (3) Poor breathability: Existing socks are often made of a single fiber material with poor breathability. Long-term wearing can easily lead to the inability to discharge foot sweat in time, increasing bacterial growth and the generation of odor.

[0006] (4) Limited comfort: The knitting density and pore structure of traditional socks are not designed reasonably, resulting in low comfort when worn. Especially in hot summer or when walking for a long time, the feet are prone to feeling stuffy and tired. Summary of the invention

[0007] The present invention provides a high-strength antibacterial and deodorizing socks, which not only improve the strength and durability of the socks, but also significantly enhance the antibacterial and deodorizing effects thereof, while ensuring good air permeability and comfort by adopting composite yarns and three-dimensional knitting technology.

[0008] The technical scheme adopted by the present invention is: a high-strength antibacterial and deodorizing socks, which are formed by blending cotton fiber, elastic fiber, nylon fiber, polyester fiber, and silver antibacterial fiber to form a composite yarn with antibacterial function, and then formed by three-dimensional knitting technology to obtain socks with microporous structures on the surface, and finally impregnated with a treatment agent to obtain finished socks.

[0009] The raw materials of the treatment agent include, by weight: 1-5 parts of nano silver ion solution, 5-10 parts of waterborne polyurethane emulsion, 3-8 parts of acrylic resin, 1-3 parts of silane coupling agent, 0.5-2 parts of UV protection agent, 0.1-0.5 parts of defoaming agent, 1-2 parts of softener and 70-80 parts of water.

[0010] As a further improvement of the present invention, the cotton fiber accounts for 40%-60% of the total weight, the elastic fiber accounts for 10%-15%, the nylon fiber accounts for 15%-20%, the polyester fiber accounts for 5%-15%, and the silver antibacterial fiber accounts for 10%-20%.

[0011] As a further improvement of the present invention, the weaving density of the three-dimensional weaving technology is 80-120 meshes per square centimeter, ensuring that the socks have good air permeability and comfort.

[0012] As a further improvement of the present invention, the solid-liquid ratio of the socks to the treatment agent is 1:(5-20), and an ultrasonic impregnation process is used to allow the treatment agent to evenly penetrate into the fiber structure of the socks, thereby enhancing the antibacterial and deodorizing effects.

[0013] As a further improvement of the present invention, the silane coupling agent is one or more combinations of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and n-dodecyltrimethoxysilane.

[0014] As a further improvement of the present invention, the UV protection agent is one or more combinations of phenyl o-hydroxybenzoate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and 2,4-dihydroxybenzophenone.

[0015] As a further improvement of the present invention, the defoaming agent is one or more combinations of polydimethylsiloxane, polyether-modified polysiloxane, and ethylene glycol siloxane.

[0016] As a further improvement of the present invention, the softener is one or more combinations of fatty alcohol polyoxyethylene ether, fatty acid amide, and polyethylene glycol fatty acid ester.

[0017] As a further improvement of the present invention, the concentration of the nano silver ion solution is 10-50 ppm.

[0018] As a further improvement of the present invention, the temperature of the treatment agent impregnation process is controlled at 30-50° C. and the time is 20-60 minutes to ensure that the treatment agent fully penetrates.

[0019] Beneficial effects of the present invention: (1) Significantly enhanced antibacterial and deodorizing properties: The socks of the present invention are treated with silver-based antibacterial fibers and nano-silver ion solution, which can effectively inhibit bacterial growth and thus reduce the generation of odor.

[0020] (2) Excellent strength and durability: The present invention scientifically mixes cotton fiber, elastic fiber, nylon fiber and polyester fiber, and applies three-dimensional knitting technology to make the socks soft and comfortable while having better mechanical strength and wear resistance, making them particularly suitable for long-term wear and outdoor sports.

[0021] (3) Excellent breathability and comfort: The use of three-dimensional knitting technology not only improves the wear resistance of the socks, but also forms a unique micro-pore structure inside the socks, creating a good air circulation environment for the soles of the feet. DETAILED DESCRIPTION

[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0023] The invention provides a high-strength antibacterial and deodorizing socks. The composite yarn with antibacterial function is formed by blending cotton fiber, elastic fiber, nylon fiber, polyester fiber and silver antibacterial fiber, and then formed by three-dimensional weaving technology to obtain socks with microporous structures on the surface. Finally, the finished socks are obtained after being impregnated with a treating agent. The raw materials of the treating agent include, by weight, 1-5 parts of nano silver ion solution, 5-10 parts of waterborne polyurethane emulsion, 3-8 parts of acrylic resin, 1-3 parts of silane coupling agent, 0.5-2 parts of ultraviolet protection agent, 0.1-0.5 parts of defoaming agent, 1-2 parts of softener and 70-80 parts of water.

[0024] In the invention, cotton fiber accounts for 40%-60% of the total weight, elastic fiber accounts for 10%-15%, nylon fiber accounts for 15%-20%, polyester fiber accounts for 5%-15%, and silver-based antibacterial fiber accounts for 10%-20%.

[0025] The three-dimensional knitting technology of the present invention has a knitting density of 80-120 meshes per square centimeter, ensuring that the socks have good air permeability and comfort.

[0026] In the present invention, the solid-liquid ratio of socks to the treatment agent is 1:(5-20), and an ultrasonic impregnation process is adopted to make the treatment agent evenly penetrate into the fiber structure of the socks, thereby enhancing the antibacterial and deodorizing effects.

[0027] In the present invention, the silane coupling agent is one or more combinations of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, and n-dodecyl trimethoxysilane. The UV protection agent is one or more combinations of o-hydroxybenzoic acid phenyl ester, 2-(2'-hydroxy-5'-methylphenyl) benzotriazole, and 2,4-dihydroxybenzophenone. The defoaming agent is one or more combinations of polydimethylsiloxane, polyether-modified polysiloxane, and ethylene glycol siloxane. The softener is one or more combinations of fatty alcohol polyoxyethylene ether, fatty acid amide, and polyethylene glycol fatty acid ester.

[0028] The concentration of the nano silver ion solution in the present invention is 10-50ppm.

[0029] The temperature of the treatment agent impregnation process in the present invention is controlled at 30-50° C. and the time is 20-60 minutes to ensure that the treatment agent fully penetrates.

[0030] Embodiment 1:

[0031] Raw material ratio: 50% cotton fiber, 12% elastic fiber (spandex), 18% nylon fiber, 8% polyester fiber, and 12% silver antibacterial fiber.

[0032] Treatment agent formula: 3 parts of nano silver ion solution (30ppm), 8 parts of water-based polyurethane emulsion, 5 parts of acrylic resin, 2 parts of silane coupling agent (γ-aminopropyltriethoxysilane), 1 part of UV inhibitor (2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole), 0.3 parts of defoaming agent (polydimethylsiloxane), 1.5 parts of softener (fatty alcohol polyoxyethylene ether), and 75 parts of water.

[0033] Preparation process:

[0034] (i) Preparation of composite yarn: The cotton fiber, elastic fiber, nylon fiber, polyester fiber and silver antibacterial fiber in the above proportions are mixed evenly and made into composite yarn using a spinning device. The fineness of the composite yarn is 30 denier (dtex) and the fiber length is 38 mm.

[0035] (ii) Three-dimensional knitting: Use a three-dimensional knitting machine to knit at a density of 100 meshes per square centimeter to form socks with a micro-pore structure. During the knitting process, special attention is paid to the reinforcement of the toes and heels, using a denser knitting density (120 meshes / square centimeter) to improve the wear resistance of these parts.

[0036] (III) Preparation of treatment agent: Nano silver ion solution, aqueous polyurethane emulsion, acrylic resin, silane coupling agent, UV protection agent, defoaming agent and softener are mixed evenly in the above proportions to prepare the treatment agent. The pH value of the treatment agent is controlled at 6.5 to ensure its stability and friendliness to the fiber.

[0037] (IV) Impregnation treatment: Place the knitted socks and the treatment agent in an ultrasonic impregnation device at a solid-liquid ratio of 1:10. Control the impregnation temperature to 40°C and the impregnation time to 45 minutes to ensure that the treatment agent evenly penetrates into the fiber structure. During the impregnation process, the ultrasonic frequency is set to 35kHz and the power is 150W to improve the efficiency of the treatment agent penetration.

[0038] (V) Post-treatment: Take out the impregnated socks and use an air dryer to dry them at 40°C for 30 minutes to remove excess moisture. Then, heat-set the dried socks at 80°C for 10 minutes to further fix the treatment agent, thus obtaining finished socks.

[0039] Embodiment 2:

[0040] Raw material ratio: 45% cotton fiber, 15% elastic fiber (spandex), 17% nylon fiber, 10% polyester fiber, and 13% silver antibacterial fiber.

[0041] Treatment agent formula: 4 parts of nano silver ion solution (20ppm), 7 parts of water-based polyurethane emulsion, 6 parts of acrylic resin, 2.5 parts of silane coupling agent (γ-methacryloxypropyltrimethoxysilane), 1.5 parts of UV inhibitor (phenyl o-hydroxybenzoate), 0.4 parts of defoaming agent (polyether modified polysiloxane), 1.8 parts of softener (fatty acid amide), and 75 parts of water.

[0042] Preparation process:

[0043] (i) Preparation of composite yarn: The cotton fiber, elastic fiber, nylon fiber, polyester fiber and silver antibacterial fiber in the above proportions are mixed evenly and made into composite yarn using a spinning device. The fineness of the composite yarn is 40 denier (dtex) and the fiber length is 35 mm.

[0044] (ii) Three-dimensional knitting: Use a three-dimensional knitting machine to knit at a density of 90 meshes per square centimeter to form socks with a micro-pore structure. During the knitting process, special attention is paid to the reinforcement of the toes and heels, using a denser knitting density (120 meshes / square centimeter) to improve the wear resistance of these parts.

[0045] (III) Preparation of treatment agent: Nano silver ion solution, water-based polyurethane emulsion, acrylic resin, silane coupling agent, UV protection agent, defoaming agent and softener are mixed evenly in the above proportions to prepare the treatment agent. The pH value of the treatment agent is controlled at 6.6 to ensure its stability and friendliness to the fiber.

[0046] (IV) Impregnation treatment: Place the knitted socks and the treatment agent in an ultrasonic impregnation device at a solid-liquid ratio of 1:12. Control the impregnation temperature to 45°C and the impregnation time to 35 minutes to ensure that the treatment agent evenly penetrates into the fiber structure. During the impregnation process, the ultrasonic frequency is set to 30kHz and the power is 200W to improve the efficiency of the treatment agent penetration.

[0047] (V) Post-treatment: Take out the impregnated socks and use an air dryer to dry them at 50°C for 25 minutes to remove excess moisture. Then, heat-set the dried socks at 85°C for 12 minutes to further fix the treatment agent, thus obtaining finished socks.

[0048] Embodiment 3:

[0049] Raw material ratio: 40% cotton fiber, 10% elastic fiber (spandex), 20% nylon fiber, 15% polyester fiber, and 15% silver antibacterial fiber.

[0050] Treatment agent formula: 2 parts of nano silver ion solution (40ppm), 9 parts of water-based polyurethane emulsion, 7 parts of acrylic resin, 2 parts of silane coupling agent (N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane), 1 part of UV protection agent (2,4-dihydroxybenzophenone), 0.2 parts of defoaming agent (ethylene glycol siloxane), 1.2 parts of softener (polyethylene glycol fatty acid ester), and 75 parts of water.

[0051] Preparation process:

[0052] (i) Preparation of composite yarn: The cotton fiber, elastic fiber, nylon fiber, polyester fiber and silver antibacterial fiber in the above proportions are mixed evenly and made into composite yarn using a spinning device. The fineness of the composite yarn is 50 denier (dtex) and the fiber length is 30 mm.

[0053] (ii) Three-dimensional knitting: Use a three-dimensional knitting machine to knit at a density of 85 meshes per square centimeter to form socks with a micro-pore structure. During the knitting process, special attention is paid to the reinforcement of the toes and heels, using a denser knitting density (120 meshes / square centimeter) to improve the wear resistance of these parts.

[0054] (III) Preparation of treatment agent: Nano silver ion solution, aqueous polyurethane emulsion, acrylic resin, silane coupling agent, UV protection agent, defoaming agent and softener are mixed evenly in the above proportions to prepare the treatment agent. The pH value of the treatment agent is controlled at 6.4 to ensure its stability and friendliness to the fiber.

[0055] (IV) Impregnation treatment: Place the knitted socks and the treatment agent in an ultrasonic impregnation device at a solid-liquid ratio of 1:12. Control the impregnation temperature to 35°C and the impregnation time to 50 minutes to ensure that the treatment agent evenly penetrates into the fiber structure. During the impregnation process, the ultrasonic frequency is set to 40kHz and the power is 180W to improve the efficiency of the treatment agent penetration.

[0056] (V) Post-treatment: Take out the impregnated socks and use an air dryer to dry them at 45°C for 35 minutes to remove excess moisture. Then, heat-set the dried socks at 82°C for 11 minutes to further fix the treatment agent, thus obtaining finished socks.

[0057] Finished product testing

[0058] In order to verify the performance of the high-strength antibacterial and deodorizing socks in Examples 1-3, the following test items were conducted: antibacterial performance, deodorizing performance, wear resistance, air permeability, UV protection performance and comfort. The test results are as follows:

[0059]

[0060] Test method description

[0061] (1) Antibacterial performance: The ISO 20743 standard is used for testing, and the antibacterial effect is evaluated by measuring the growth of microorganisms on the surface of socks.

[0062] (2) Anti-odor performance: The ASTM E2126 standard was used for testing, and the changes in odor concentration of socks under simulated usage conditions were measured using a gas analyzer.

[0063] (3) Wear resistance: The AATCC 93 standard is used for testing. The wear tester is used to simulate the wear of socks during wearing and the wear cycle is recorded.

[0064] (4) Breathability: The ASTM E96 standard is used to test the breathability of socks by measuring their moisture permeability.

[0065] (5) Ultraviolet protection performance: The ISO 13758 standard is used for testing. The ultraviolet protection ability of the socks is measured using a UV transmittance tester to evaluate the UPF value.

[0066] (6) Comfort: The temperature and humidity sensors are used to measure the temperature changes of the feet while the device is being worn to assess the comfort level.

[0067] (7) Finished product appearance: Visual inspection to evaluate color uniformity and appearance consistency.

[0068] (8) Elasticity: The elastic recovery rate of the socks was measured using a tensile testing machine to evaluate their elastic properties.

[0069] (9) Dimensional stability: The dimensional stability of socks is evaluated by measuring the dimensional changes before and after washing.

[0070] (10) Washing stability: After 10 standard washes, the antibacterial properties of the socks were measured again to evaluate their washing stability.

[0071] It can be seen from the above test results that the high-strength antibacterial and anti-odor socks in Examples 1-3 all exhibit excellent antibacterial and anti-odor performance, wear resistance, air permeability and comfort. In particular, the enhanced treatment of the toes and heels significantly improves the wear resistance of these parts, making them suitable for long-term wear and outdoor sports. In addition, the impregnation process of the treatment agent effectively improves the antibacterial and anti-odor effect of the socks, and can still maintain a high antibacterial rate after multiple washings.

[0072] In summary, the high-strength antibacterial and deodorant socks of the present invention have successfully achieved multiple functions such as high strength, antibacterial and deodorant through scientific raw material ratios and advanced production processes. The appearance of the socks is uniform and consistent, without color difference, meeting the requirements of high-quality products. Its good elasticity and dimensional stability ensure the comfort and durability of wearing. After multiple washing tests, the antibacterial properties of the socks remain at a high level, showing excellent washing stability. Combining various performance indicators, the high-strength antibacterial and deodorant socks of the present invention not only meet the needs of daily wear, but also show excellent performance under specific environments, and have broad market application prospects.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength antibacterial and deodorizing socks, characterized in that: The composite yarn with antibacterial function is formed by blending cotton fiber, elastic fiber, nylon fiber, polyester fiber and silver antibacterial fiber, and then formed by three-dimensional knitting technology to obtain socks with tiny pores on the surface. Finally, the finished socks are obtained after being impregnated with a treatment agent. The raw materials of the treatment agent include, by weight: 1-5 parts of nano silver ion solution, 5-10 parts of waterborne polyurethane emulsion, 3-8 parts of acrylic resin, 1-3 parts of silane coupling agent, 0.5-2 parts of UV protection agent, 0.1-0.5 parts of defoaming agent, 1-2 parts of softener and 70-80 parts of water.

2. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The cotton fiber accounts for 40%-60% of the total weight, the elastic fiber accounts for 10%-15%, the nylon fiber accounts for 15%-20%, the polyester fiber accounts for 5%-15%, and the silver antibacterial fiber accounts for 10%-20%.

3. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The three-dimensional weaving technology has a weaving density of 80-120 meshes per square centimeter, ensuring that the socks have good air permeability and comfort.

4. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The solid-liquid ratio of the socks to the treatment agent is 1:(5-20), and an ultrasonic impregnation process is adopted to make the treatment agent evenly penetrate into the fiber structure of the socks, thereby enhancing the antibacterial and deodorizing effects.

5. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The silane coupling agent is one or more combinations of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and n-dodecyltrimethoxysilane.

6. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The anti-ultraviolet agent is one or more combinations of phenyl o-hydroxybenzoate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 2,4-dihydroxybenzophenone.

7. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The defoaming agent is one or more combinations of polydimethylsiloxane, polyether-modified polysiloxane and ethylene glycol siloxane.

8. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The softener is one or more combinations of fatty alcohol polyoxyethylene ether, fatty acid amide, and polyethylene glycol fatty acid ester.

9. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The concentration of the nano silver ion solution is 10-50ppm.

10. The high-strength antibacterial and deodorizing socks according to claim 1, characterized in that: The temperature of the treatment agent impregnation process is controlled at 30-50° C. and the time is 20-60 minutes to ensure that the treatment agent fully penetrates.